Percorsi partecipativi di valutazione in P.I.P.P.I.: possibilità per una riconfigurazione dei significati di evidenza scientifica - Serbati, Sara (Rivista Italiana di Educazione Familiare, 2017)
Evaluation is constantly requested by governments and decision-makers, to prove that social policies and actions undertaken are effective in responding to problems. Also P.I.P.P.I. Programme is involved in such request to find strategies for guaranteeing that children enjoy their childhood and ensure access to quality service. But, in the past years several reports highlighted the gap between knowledge of effective treatments and practices delivered. Reflecting on P.I.P.P.I. experience through the evaluation models now existing in literature, the article aims to highlight the key points that have made the programme successful. It will be introduced an innovative understanding of knowledge to be investigated by evaluation, not only developed externally from practices, but also built internally, through reflective and dialogical activities. It has been introduced a new understanding of scientific evidence, able to give internal legitimacy to people’s actions, thus understanding the conditions needed to fill the gap between knowledge and practice. It builds a new conception of evidence, no longer understood only as “what works” (external evidence), but also as processes able to produce change in people’s decision making (internal evidence) that happens within reflective and dialogical contexts (communicative evidence).